Blockade of Cyclophilin D Attenuates Oxidative Stress-Induced Cell Death in Human Dental Pulp Cells. (4th April 2019) - Huang, Shengbin; Zheng, Bingbing; Jin, Xing; Yu, Qihao; Zhang, Xiaorong; Sun, Xiaoyu; Chen, Yuting; Ren, Xuerui; Wismeijer, Daniel; Ma, Jianfeng; Zhang, Chengfei; Wu, Gang; et al.
Abstract : Pathological stimuli, such as bacterial activity, dental bleaching, and nonpolymerized resin monomers, can cause death of dental pulp cells (DPCs) through oxidative stress- (OS-) induced mitochondrial dysfunction. However, the crucial molecular mechanisms that mediate such a phenomenon remain largely unknown. OS is characterized by the overproduction of reactive oxygen species (ROS), e.g., H2 O2, O2 −, and ⋅ OH. Mitochondria are a major source of ROS and the principal attack target of ROS. Cyclophilin D (CypD), as the only crucial protein for mitochondrial permeability transition pore (mPTP) induction, facilitates the opening of mPTP and causes mitochondrial dysfunction, leading to cell death. In the present study, we hypothesized that CypD-mediated mitochondrial molecular pathways were closely involved in the process of OS-induced death of human DPCs (HDPCs). We tested the phenotypic and molecular changes of HDPCs in a well-established OS model—H2 O2 treatment. We showed that H2 O2 dramatically reduced the viability and increased the death of HDPCs in a time- and dose-dependent manner by performing MTT, flow cytometry, and TUNEL assays and quantifying the expression changes of Bax and Bcl-2 proteins. H2 O2 also induced mitochondrial dysfunction, as reflected by the increased mitochondrial ROS, reduced ATP production, and activation of mPTP (decreased mitochondrial membrane potential and enhanced intracellular Ca 2+ level). An antioxidant (N-acetyl-L-cysteine) effectively preserved mitochondrial function and significantly attenuated H2 O2 -induced cytotoxicity and death. Moreover, H2 O2 treatment markedly upregulated the CypD protein level in HDPCs. Notably, genetic or pharmacological blockade of CypD significantly attenuated H2 O2 -induced mitochondrial dysfunction and cell death. These findings provided novel insights into the role of a CypD-dependent mitochondrial pathway in the H2 O2 -induced death in HDPCs, indicating that CypD may be a potential therapeutic target to prevent OS-mediated injury in dental pulp.